1979
DOI: 10.1210/endo-104-2-350
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms in Adrenal Responsiveness to Adrenocorticotropin Are Determined Primarily by the Time of Feeding in the Rat*

Abstract: These experiments were done to determine: 1) whether feeding-related shifts in daily corticosterone rhythms are dependent upon changes in ACTH rhythms, 2) whether restricted feeding of rats results in abnormally high ACTH and corticosterone levels (i.e. stress), and 3) whether changes in either insulin or glucose levels might be the concomitants of feeding that change adrenal responsiveness to ACTH. Young male rats (80--90 g) on a 12-h light, 12-h dark cycle were allowed access to one of three diets for 2 h/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
50
2
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 36 publications
12
50
2
1
Order By: Relevance
“…Analysis of diurnal events that precede the increasing phases of apo A-IV expression may help us to identify the regulatory factor/s of diurnal expression of apo A-IV mRNA and protein. In a carefully conducted study described by Wilkinson et al (29), peak Cort levels occurred just before feeding, making Cort a potential regulator of intestinal apo A-IV. Consistent with this report, we observed that a single peak in plasma Cort levels occurred just before the active feeding period (the dark cycle).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of diurnal events that precede the increasing phases of apo A-IV expression may help us to identify the regulatory factor/s of diurnal expression of apo A-IV mRNA and protein. In a carefully conducted study described by Wilkinson et al (29), peak Cort levels occurred just before feeding, making Cort a potential regulator of intestinal apo A-IV. Consistent with this report, we observed that a single peak in plasma Cort levels occurred just before the active feeding period (the dark cycle).…”
Section: Discussionmentioning
confidence: 99%
“…The control of the circadian rhythm in corticosterone release might be effected either via changes in its central drive (i.e., secretion of CRH and ACTH) or by changes in the adrenal sensitivity to ACTH (Wilkinson et al, 1979;Kaneko et al, 1981;Charlton, 1990). To investigate further the neural mechanisms underlying the circadian control of corticosterone release, we also measured plasma ACTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the corticosterone data, ACTH levels showed no diurnal variation during the different Ringer's infusions ( p Ͼ 0.5), although variability during the CT10 experiment was considerably higher than at any other time of the day (16.8 Ϯ 2.8 vs 6.8 Ϯ 1.9, 7.6 Ϯ 2.3, 10.6 Ϯ 1.1, and 11.0 Ϯ 2.4 pg/ml). A number of previous studies have reported diurnal variations in plasma ACTH levels Carnes et al, 1989;Bagdy et al, 1991;Kwak et al, 1992;Ixart et al, 1993), but quite a few others failed to detect significant diurnal variations (Wilkinson et al, 1979;Akana et al, 1986;Carnes et al, 1986;Cascio et al, 1987;Kwak et al, 1993;Suemaru et al, 1995). Important factors that may contribute to the difficulty of finding a circadian ACTH rhythm are the low amplitude of the rhythm, the episodic secretion of ACTH, the sampling protocol used (Carnes et al, 1986;Turek and Van Cauter, 1988;Carnes et al, 1989), and the assay variability (e.g., CT times in different assays).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade the role of timing of food provision as an entrainer has been proposed for laboratory rodents. This is based on the findings that in rats (3)(4)(5) and mice (6) the phase of the plasma corticosterone rhythm shifts when the feeding time is changed and that the peak of the corticosterone level appeared just before the feeding time regardless of lighting conditions. In human subjects, however, such a synchronizing role of meal intake is controversial.…”
Section: Discussionmentioning
confidence: 99%